Pengaruh Return On Asset, Return On Equity Dan Net Profit Margin Terhadap Pertumbuhan Laba Pada Perusahaan Rokok Yang Terdaftar Di Bursa Efek Indonesia Periode 2019-2021 - Ferdiansyah Dista Pratama Putra; Ustadus Sholihin; Zulfia Rahmawati (International Forum of Researchers and Lecturers, 2023)
The development of the business world and increasingly rapid economic developments encourage business competitors to improve company performance. The establishment of a company must have clear goals. To achieve the company's goal of making a profit, various strong supporting factors are needed, one of which is good funding management. Determining the optimal level of capital structure is a funding decision in achieving company goals. This research aims to determine the partial and simultaneous influence between Return On Assets, Return On Equity and Net Profit Margin on Profit Growth in Cigarette Companies Listed on the Indonesian Stock Exchange for the 2019-2021 Period.This research is descriptive research with a quantitative approach. The data source used is a secondary data source originating from the Indonesian Stock Exchange website. The sampling technique in this research used the purposive sampling method. The research results show that the Return On Asset variable has no influence on Profit Growth in Cigarette Companies listed on the Indonesia Stock Exchange 2019-2021, then the Return On Equity variable has no influence on Profit Growth in Cigarette Companies listed on the Indonesia Stock Exchange 2019-2021 , then the Net Profit Margin variable has no influence on Cigarette Companies listed on the Indonesia Stock Exchange 2019-2021, and Return On Assets, Return On Equity, and Net Profit Margin simultaneously have an influence on Profit Growth in Cigarette Companies listed on the Stock Exchange Indonesia 2019-2021.